Clinical application of the tibial extension stem in primary TKA for knee varus deformity combined with tibial bone defect - Yuan, Fei; Li, Yankun; Shen, Xiaogang; Zhu, Xuepeng; Sun, Li; Ren, Youliang; Guo, Tao; Li, Bo (Frontiers in Surgery, 2025)
ObjectiveTo observe the clinical efficacy of prophylactic use of tibial extension stem in primary Total Knee Arthroplasty (TKA) in patients with severe knee varus deformity and tibial plateau bone defect, and its effect on reducing the rate of tibial prosthesis aseptic loosening.MethodsA total of 398 patients who underwent primary TKA in our hospital from August 2019 to June 2021 were collected. According to the strict inclusion/exclusion criteria, 55 patients with knee varus deformity (Hip-knee-ankle Angle, HKA ≤ 160°) and tibial bone defect were finally included. The tibial extension stem was used in 22 patients and standard tibial prosthesis was used in 33 patients. The general data, intraoperative parameters, preoperative and postoperative imaging parameters and knee function scores (KSS) were analyzed. The incidence of tibial prosthesis aseptic loosening, KSS score, radiological evaluation of the prosthesis and bone cement screws, and postoperative general complications were dynamically followed up and evaluated.ResultsAll 55 patients completed long-term follow-up, with an average follow-up time of 46.1 ± 4.2 months. There was no significant difference in HKA Angle between the two groups before and after operation (p > 0.05). At least 36 months follow-up, The final Society Radiographic Evaluation System (KSRES) scores were significantly different in the range of 4–10 mm (p < 0.05), but no screw loosening, sinking, osteolysis, bone cement fracture and serious postoperative complications occurred in all patients. There was no significant difference in KSS scores between the two groups during the follow-up period (p > 0.05). At the end of follow-up, there was no aseptic loosening of tibial prosthesis and serious postoperative complications in both groups.ConclusionsFor patients with severe knee varus deformity and tibial plateau bone defect, the use of tibial extension stem in primary TKA may have a protective effect on the survival rate of prosthesis.